Unlocking hybrid electrokinetic opportunities for soils restoration and addressing current challenges - Muhammad Imran; Kainat Anwer; Samiullah Akram; Nageen Kousar; Abdul Ahad Hussain; Jinsheng Zhao; Limin Wang (Process Safety and Environmental Protection, 2026)

FlgE–TLR5 interaction and its association with immune and microbiota responses in Asian swamp eel fed Bacillus velezensis - Nourhan Nassar; Ibrar Muhammad Khan; Samiullah Khan; Abdul Qadeer; Ni Du; Zaigui Wang (Fish & Shellfish Immunology, 2026)

Mapping soil microplastics across land uses: a baseline survey from northwestern Türkiye - Meral Yurtsever; Samiullah Serat; Sema Dalkıran; Esra Gülen (Environmental Monitoring and Assessment, 2026)

Corrigendum to “Next generation nutraceuticals from Torreya grandis bioactive peptides enabled by green extraction and biotechnological innovation toward future applications” [Trends in Food Science & Technology 172 (2026) 105717] - Rabia Durrani; Duo Xu; Mohamed A. Farag; Samiullah Khan; Erwann Durand; Hammad Ullah; Fei Gao; Jiasheng Wu; Lili Song (Trends in Food Science & Technology, 2026)

Next generation nutraceuticals from Torreya grandis bioactive peptides enabled by green extraction and biotechnological innovation toward future applications - Rabia Durrani; Duo Xu; Mohamed A. Farag; Samiullah Khan; Erwann Durand; Hammad Ullah; Fei Gao; Jiasheng Wu; Lili Song (Trends in Food Science & Technology, 2026)

Effects of dietary ammonium chloride in late gestation on farrowing performance and piglet survival - Thien D Van; Roy N Kirkwood; Mariana Caetano; Do T Hue; Gebremeskel M Werid; AHM Musleh Uddin; Samiullah Khan; Kiro R Petrovski (Livestock Science, 2026)

Impacts of digestate recycling as inoculum in percolate-recirculated high-solids anaerobic digestion of source separated organics: Multi-cycle assessment - Anindya Amal Chakrabarty; Samiullah Khaskheli; Sherif Ismail; Simran Kaur Dhillon; Tae Hyun Chung; Bipro Ranjan Dhar (Process Safety and Environmental Protection, 2026)

CRISPR-Cas9 and next-generation gene editing strategies for therapeutic intervention of neurodegenerative pathways in Alzheimer’s disease: a state-of-the-art review - Muhammad Sohail Khan; Imran Zafar; Adil Jamal; Fayez Saeed Bahwerth; Samiullah Khan; Muhammad Faizan; Hanif Khan; Muhammad Noman; Kendrix Okeibunor; Ashfaq Ahmad; Muhammad Zain Ul Abedin (Acta Neurologica Belgica, 2026)

Bacteriophage-Based Vaccine Platform for Next Generation Vaccine Development Against Bovine Tuberculosis and Other Pulmonary Diseases of Animals - Shahzar Khan; Nadia Ilyas; Fida Ullah Khan; Aneela Nawaz; Mohammed Raashid; Muhammad Ismail Khan; Momina Aamir; Aamer Ali Shah; Malik Badshah; Brekhna Alam; Samiullah Khan (International Journal of Peptide Research and Therapeutics, 2026)

Anti-arthritic and anti-inflammatory effects of BMZD-2CPE in a CFA and carrageenan-induced animal model - Samiullah Wazir; Farah Abid; Aisha Mobashar; Arham Shabbir; Muhammad Awais; Humaira Nadeem; Hafiz Aamir Ali Kharl; Esmael M. Alyami; Amir Bouallegue; Norah Hamdi; Mohammed Bourhia; Abdullah R. Alanzi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Strategies for mitigating carbon dioxide emissions: advanced carbon capture and storage technologies - Maria Safdar; Aqsa Mushtaq; Samiullah Akram (Environmental Science and Pollution Research, 2026)

Bacteriophage-based vaccination platform for antigen discovery and development of next-generation vaccines - Shahzar Khan; Nadia Ilyas; Aneela Nawaz; Muhammad Ismail Khan; Momina Aamir; Nauman Ahmed Khalid; Aamer Ali Shah; Numan Saleh Zada; Ghulam Shabbir; Malik Badshah; Samiullah Khan (Next Research, 2025)

Improving high-solids anaerobic digestion of source-separated organics with nanobubble water supplementation: Significance of microbial community dynamics - Samiullah Khaskheli; Anindya Amal Chakrabarty; Samruddhi Sali; Tae Hyun Chung; Sherif Ismail; Bipro Ranjan Dhar (Bioresource Technology Reports, 2025)

First report of Alternaria alternata causing leaf blotch and fruit spot of apple in Pakistan - Sami Ullah; Samiullah; Naseer Ahmed; Muhammad Kamran; Muhammad Ibrahim; Safdar Ali; Adnan Kashif (New Zealand Journal of Botany, 2025)

Ter-polymeric Cytocompatible Hydrogels Based on Sodium Alginate with Pectin and Acrylic Acid for Controlled Loxoprofen Sodium Oral Delivery; In vitro and In vivo Evaluation - Samiullah Khan; Abdur Rehman; Syed Faisal Badshah; Muhammad Saad (Journal of Pharmaceutical Innovation, 2025)

Isolation and Characterization of Aspergillus niger AZ2 from Pulp and Paper Mill Effluent that Degrade Lignin under Alkaline Conditions - Alam Z. Khan; Salah U. Din; Mehmoona Sharif; Fariha Hasan; Samiullah Khan; Malik Badshah; Ali O. Beldüz; Aamer A. Shah (Current Microbiology, 2025)

Machine learning-driven docking of diverse DDAs as promising cysteine protease inhibitors targeting Mpox virus - Bader S. Alotaibi; Irfan Ahmad; Bandar Almutairy; Abdullah Alkhammash; Ahad Amer Alsaiari; Kanwal Khan; Samiullah Burki (In Silico Pharmacology, 2025)

Exploring the hidden world of muskmelon miRNAs: experimental hunts of computational predicted miRNAs and their protein targets - Abdul Ghaffar; Naqeebullah Khan; Irshad Ali; Attiq ur Rehman; Samiullah; Waheed Ahmed Shah; Muhammad Javed Khan (Genetic Resources and Crop Evolution, 2025)

Recent updates on drug delivery approaches for improved ocular delivery with an insight into nanostructured drug delivery carriers for anterior and posterior segment disorders - Samiullah Khan; Chi-Wai Do; Emmanuel A. Ho (Drug Delivery and Translational Research, 2025)

Bioactive Metabolites from Radioresistant Bacterium Kocuria sp. TMM 11 and Their Role in Prevention of Ultraviolet-Induced Photodamages - Tayyaba Alam; Salah Ud Din; Muhammad Abdullah; Mahwish Ali; Malik Badshah; Muhammad Farman; Samiullah Khan; Fariha Hasan; Aamer Ali Shah (Current Microbiology, 2025)

Identification and Characterization of Evolutionary Conserved Muskmelon Non-coding miRNAs and Their Target Proteins - Abdul Ghaffar; Naqeebullah khan; Muhammad Zafar Saleem; Irshad Ali; Attiq Ur Rehman; Waheed Ahmed Shah; Samiullah (Biochemical Genetics, 2025)

Genome-wide analysis of CNGC gene family in Brassica juncea (L.) Czern reveals key targets for stress resistance and crop improvement - Akram Ali Baloch; Kaleem U. Kakar; Sumera Rais; Zarqa Nawaz; Abdulwareth A. Almoneafy; Agha Muhammad Raza; Samiullah Khan; Raqeeb Ullah (Plant Gene, 2025)

Tolerance pattern against the heavy metals and pesticides in Escherichia coli isolated from water samples - Safia Mustafa; Attiq Ur Rehman Kakar; Yasmeen Malik; Naqeebullah Khan; Samiullah (Brazilian Journal of Microbiology, 2025)

Exploring the diversity of scorpions in Lahore Division, Punjab: an ecological approach - Muhammad Mohsin Ahsan; Abdul Khalaq; Hafiz Muhammad Tahir; Muhammad Ismail; Muhammad Samiullah; Maira Noor; Safia Bibi (International Journal of Tropical Insect Science, 2025)

Reshaping the healthcare world by AI-integrated wearable sensors following COVID-19 - Bangul Khan; Rana Talha Khalid; Khair Ul Wara; Muhammad Hasan Masrur; Samiullah Khan; Wasim Ullah Khan; Umay Amara; Saad Abdullah (Chemical Engineering Journal, 2025)

Assessment of HER1 (rs11543848) and HER2 (rs1136201) polymorphism and their association with colorectal cancer susceptibility in Khyber Pakhtunkhwa, Pakistan - Asad Ullah; Bibi Maryam Khan; Najeeb Ullah Khan; Sidra Tul Muntaha; Samiullah Khan; Aakif Ullah Khan; Mikhlid H. Almutairi; Ijaz Ali (Molecular Biology Reports, 2024)

Correction: Soil Liming Ameliorates Crude Oil Stress and Promotes Biochemical Indices and Photosynthetic and Antioxidant Enzyme Activities in Lemongrass (Cymbopogon citratus) - Naila Ali; Kehinde Olajide Erinle; Aniqa Amber Sher; Zaib-un-Nisa; Sayed Samiullah Hakimi; Beenish Afzal; Yasin M. Ashraf (Journal of Soil Science and Plant Nutrition, 2024)

Identification and characterization of functional microRNAs and their significant targets in maize plants - Abdul Baqi; Samiullah; Ghulam Mustafa Khan; Asadullah; Naqeebullah Khan; Attiq-Ur-Rehman; Alia Ahmed (Journal of Plant Biochemistry and Biotechnology, 2024)

In-vivo assessment of wound healing activity of halibut oil cream in rat model of excision wound - S. T. Shukla; Anu Kaushik; Samiullah Allahbaksh Auti; Dinesh Kumar; Supriya Kumar Das (Advances in Traditional Medicine, 2024)

Effect of Perilla seeds inclusion on the performance, egg quality characteristics, biochemical parameters and egg yolk fatty acid composition of laying hens - Ping Li; Samiullah Khan; Yanhua Huang; Shengtao Lu; Panhong Zhou; Jiale Ling; Tianzheng Xu; Xiaoli Shi (Tropical Animal Health and Production, 2024)

Aspongopus chinensis ach-miR-276a-3p induces breast cancer cell cycle arrest by targeting APPL2 to regulate the CDK2-Rb-E2F1 signaling pathway - Renlian Cai; Samiullah Khan; Xumei Chen; Haiyin Li; Jun Tan; Ying Tian; Shuai Zhao; Zhiyong Yin; Tongxian Liu; Daochao Jin; Jianjun Guo (Toxicology and Applied Pharmacology, 2024)

Identification and Annotation of the 21 Novel Sugar Cane (Saccharum officinarum) MicroRNA Clusters and Their Significant Biological, Molecular and Cellular Targets - Abdul Baqi; Samiullah; Muhammad Zafar Saleem; Muhammad Ayub; Shazia Saeed (Tropical Plant Biology, 2024)

Effect of removal of inhibitors on microbial communities and biogas yield of Jatropha curcas seeds during continuous anaerobic digestion - Abdul Haq; Ayesha Malik; Alam Khan; Joseph E. Weaver; Ling Wang; Haji Khan; Samiullah Khan; Aamer Ali Shah; Safia Ahmed; Asif Jamal; Francis L. de los Reyes; Malik Badshah (Journal of Cleaner Production, 2023)

Soil Liming Ameliorates Crude Oil Stress and Promotes Biochemical Indices and Photosynthetic and Antioxidant Enzyme Activities in Lemongrass (Cymbopogon citratus) - Naila Ali; Kehinde Olajide Erinle; Aniqa Amber Sher; Zaib-un-Nisa; Sayed Samiullah Hakimi; Beenish Afzal; Yasin M. Ashraf (Journal of Soil Science and Plant Nutrition, 2023)

Experimental behaviour of unreinforced and confined rat-trap bond masonry - Muhammad Haris; Mohammad Ashraf; Muhammad Fahim; Samiullah (European Journal of Environmental and Civil Engineering, 2023)

Significant association of BRCA1 (rs1799950), BRCA2 (rs144848) and TP53 (rs1042522) polymorphism with breast cancer risk in Pashtun population of Khyber Pakhtunkhwa, Pakistan - Yumna Khan; Najeeb Ullah Khan; Ijaz Ali; Samiullah Khan; Aakif Ullah Khan; Aqib Iqbal; Brian D. Adams (Molecular Biology Reports, 2023)

Investigation of a gel-based delivery method for the administration of a live, attenuated Salmonella Typhimurium vaccine - Siyuan Jia; Andrea R. McWhorter; Samiullah Khan; Daniel M. Andrews; Gregory J. Underwood; Kapil K. Chousalkar (Veterinary Microbiology, 2023)

Synthetic star shaped tetra-tailed biocompatible supramolecular amphiphile as an efficient nanocarrier for Amphotericin B - Imdad Ali; Samiullah Burki; Jawad ur Rehman; Shafi Ullah; Ibrahim Javid; Magda H. Abdellattif; Muhammad Raza Shah (Chemistry and Physics of Lipids, 2023)

Chemical mutagenesis: role in breeding and biofortification of lentil (Lens culinaris Medik) mutant lines - Aamir Raina; Mohammad Rafiq Wani; Rafiul Amin Laskar; Samiullah Khan (Molecular Biology Reports, 2022)

Assessing the sustainability and cost-effectiveness of concrete incorporating various fineness of eggshell powder as supplementary cementitious material - Ashfaque Ahmed Jhatial; Aneel Kumar; Naraindas Bheel; Samiullah Sohu; Wan Inn Goh (Environmental Science and Pollution Research, 2022)

Experimental and numerical seismic assessment of non-ductile reinforced concrete (RC) columns strengthened with glass fiber reinforced polymer (GFRP) - Kittipoom Rodsin; Tahir Mehmood; Kristijan Kolozvari; Adnan Nawaz; Qazi Samiullah; Rattapoohm Parichatprecha (Bulletin of Earthquake Engineering, 2022)

Sustainability and mechanical property assessment of concrete incorporating eggshell powder and silica fume as binary and ternary cementitious materials - Samiullah Sohu; Naraindas Bheel; Ashfaque Ahmed Jhatial; Abdul Aziz Ansari; Irfan Ali Shar (Environmental Science and Pollution Research, 2022)

Impact of soil sealing on the genesis of pluvial flood in Peshawar, Pakistan - Attaullah Khan; Atta-ur-Rahman; Samiullah; Muhammad Ayub (Arabian Journal of Geosciences, 2022)

Combined effect of coconut shell and sugarcane bagasse ashes on the workability, mechanical properties and embodied carbon of concrete - Naraindas Bheel; Samiullah Sohu; Ashfaque Ahmed Jhatial; Nafees Ahmed Memon; Aneel Kumar (Environmental Science and Pollution Research, 2022)

Inhibition of jack bean urease by amphiphilic peptides - Zafar Ali Shah; Sadam Hussain; Serab Khan; Nawab Ali; Samiullah Burki; Syed Uzair Ali Shah; Ashfaq Ahmad; Faiz -Ur-Rehman; Muhammad Nasimullah Qureshi; Syed Muhammad Mukrram Shah; Farzana Shaheen (Medicinal Chemistry Research, 2021)

Evaluation of phytochemical, bioactive, and antifungal potential of Jatropha curcas seed oil and de-oiled seed cake extracts against phytopathogenic fungi - Abdul Haq; Sama Mushtaq; Alam Khan; Arshad Islam; Haji Khan; Zulfiqar Ali Malik; Farhan Younas; Samiullah Khan; Aamer Ali Shah; Malik Badshah (Journal of Plant Pathology, 2021)

Isolation and functional characterization of exopolysaccharide produced by Lactobacillus plantarum S123 isolated from traditional Chinese cheese - Muhammad Saleem; Samiullah Malik; Hafiza Mahreen Mehwish; Muhammad Waqas Ali; Nazim Hussain; Mohsin Khurshid; Muhammad Shahid Riaz Rajoka; Yougen Chen (Archives of Microbiology, 2021)

Screening of Lipase-Producing Bacteria and Optimization of Lipase-Mediated Biodiesel Production from Jatropha curcas Seed Oil Using Whole Cell Approach - Abdul Haq; Sana Adeel; Alam Khan; Qurrat ul ain Rana; Muhammad Adil Nawaz Khan; Muhammad Rafiq; Muhammad Ishfaq; Samiullah Khan; Aamer Ali Shah; Fariha Hasan; Safia Ahmed; Malik Badshah (BioEnergy Research, 2020)

Identification of irrigation potential areas, using multi-criteria analysis in Khyber District, Pakistan - Muhammad Waleed; Sajid Rashid Ahmad; Muhammad Asif Javed; Saifullah Samiullah (Environmental Science and Pollution Research, 2020)

Precipitation variability and its trend detection for monitoring of drought hazard in northern mountainous region of Pakistan - Imran Khan; Tahir Waqas; Samiullah; Safi Ullah (Arabian Journal of Geosciences, 2020)

Antioxidative and Radioprotective Properties of Glycosylated Flavonoid, Xanthorhamnin from Radio-Resistant Bacterium Bacillus indicus Strain TMC-6 - Ayesha Ahmed Chaudhri; Mahnoor Nadeem; Asim ur Rahman; Tayyaba Alam; Wasim Sajjad; Fariha Hasan; Malik Badshah; Samiullah Khan; Fazal Rehman; Aamer Ali Shah (Current Microbiology, 2020)

Earliest-known intentionally deformed human cranium from Asia - Xijun Ni; Qiang Li; Thomas A. Stidham; Yangheshan Yang; Qiang Ji; Changzhu Jin; Khizar Samiullah (Archaeological and Anthropological Sciences, 2020)

Paleogene mammalian fauna exchanges and the paleogeographic pattern in Asia - Xijun Ni; Qiang Li; Chi Zhang; Khizar Samiullah; Limin Zhang; Yangheshan Yang; Wenxin Cao (Science China Earth Sciences, 2020)

Induction of morphological mutations and mutant phenotyping in black gram [Vigna mungo (L.) Hepper] using gamma rays and EMS - Sonu Goyal; Mohammad Rafiq Wani; Rafiul Amin Laskar; Aamir Raina; Ruhul Amin; Samiullah Khan (Vegetos, 2019)

Preparation and characterization of resistant starch type III from enzymatically hydrolyzed maize flour - Anum Khan; Ubaid Ur Rahman; Samiya Siddiqui; Muhammad Irfan; Aamer Ali Shah; Malik Badshah; Fariha Hasan; Samiullah Khan (Molecular Biology Reports, 2019)

Evaluation of microneedles-assisted in situ depot forming poloxamer gels for sustained transdermal drug delivery - Samiullah Khan; Muhammad Usman Minhas; Ismaiel A. Tekko; Ryan F. Donnelly; Raghu Raj Singh Thakur (Drug Delivery and Translational Research, 2019)

Environmental and economic impacts of better cotton: a panel data analysis - Sundas Zulfiquar; Muhammad Asim Yasin; Khuda Bakhsh; Rafaqet Ali; Samiullah; Saad Munir (Environmental Science and Pollution Research, 2019)

Natural and synthetic polymer-based smart biomaterials for management of ulcerative colitis: a review of recent developments and future prospects - Muhammad Sohail; Mudassir; Muhammad Usman Minhas; Shahzeb Khan; Zahid Hussain; Marcel de Matas; Syed Ahmed Shah; Samiullah Khan; Mubeen Kousar; Kaleem Ullah (Drug Delivery and Translational Research, 2019)

pH/Thermo-Dual Responsive Tunable In Situ Cross-Linkable Depot Injectable Hydrogels Based on Poly(N-Isopropylacrylamide)/Carboxymethyl Chitosan with Potential of Controlled Localized and Systemic Drug Delivery - Samiullah Khan; Naveed Akhtar; Muhammad Usman Minhas; Syed Faisal Badshah (AAPS PharmSciTech, 2019)

Climate‐induced hydrological variation controls the transformation of dissolved organic matter in a subalpine lake - Elisabet Ejarque; Samiullah Khan; Gertraud Steniczka; Jakob Schelker; Martin J. Kainz; Tom J. Battin (Limnology and Oceanography, 2018)
Lakes are an inherent component of the global carbon cycle. They receive dissolved organic matter (DOM) from the catchment, which is stored, transformed and respired, or delivered downstream. In this study, we show that a subalpine lake shifts its role from DOM “transporter” to “transformer” depending on season and climate. We monitored dissolved organic carbon (DOC) concentration and DOM optical properties at the inlet and outlet of subalpine Lake Lunz (Austria) at high frequency during two contrasting years: an extreme drought in 2015, and regular precipitation regime in 2016. During both years, the DOC mass balance revealed that inflowing and outflowing DOC loads were nearly balanced (+6.57% and +1.70% DOC production in 2015 and 2016, respectively). However, DOM optical properties revealed an in‐lake turnover of DOM compounds, so that the terrestrial and aromatic signature of inflowing DOM was modified into autochthonous, protein‐like DOM. The magnitude of this transformation varied seasonally, being maximal in summer and minimal in winter, presumably following periods of high and low primary production and photo‐degradation. Inter‐annually, we found that drought further increased DOM transformation during summer by extending the lake water residence time. Finally, our results demonstrate a rapid response of DOM dynamics to hydrological and meteorological changes at both seasonal and inter‐annual scales, suggesting that carbon cycling in clear‐water mountain lakes may be highly sensitive to hydrological variation.

Alkali-Activated Boiler Fly Ash for Ni(II) Removal: Characterization and Parametric Study - Muhammad Samiullah; Zaheer Aslam; Adeem Ghaffar Rana; Aamir Abbas; Waqar Ahmad (Water, Air, & Soil Pollution, 2018)

Spatial and temporal variation of rainfall and drought in Khyber Pakhtunkhwa Province of Pakistan during 1971–2015 - Ghani Rahman; Atta-ur-Rahman; Samiullah; Muhammad Dawood (Arabian Journal of Geosciences, 2018)

Cloning, antibody production, expression and cellular localization of universal stress protein gene (USP1-GFP) in transgenic cotton - Sameera Hassan; Tahir Rehman Samiullah; Mahmood ur Rahman Ansari; Bushra Rashid; Tayyab Husnain (Journal of Plant Biochemistry and Biotechnology, 2017)

An overview of phytochrome: An important light switch and photo-sensory antenna for regulation of vital functioning of plants - Abdul Qayyum Rao; Muhammad Azmat Ullah Khan; Naila Shahid; Salah ud Din; Ambreen Gul; Adnan Muzaffar; Saira Azam; Tahir Rehman Samiullah; Fatima Batool; Ahmad Ali Shahid; Idrees Ahmad Nasir; Tayyab Husnain (Biologia, 2015)

Molecular insights to explore abietane diterpenes as new LOX inhibitors - Inamullah Khan; Muhammad Nisar; Armando Zarrelli; Giovanni Di Fabio; Farah Gul; Syed Naeemuddin Gilani; Muhammad Raza Shah; Amir Zada Khan; Samiullah; Hazrat Amin (Medicinal Chemistry Research, 2013)

The diversity of Rhizobia, Sinorhizobia and novel non-Rhizobial Paenibacillus nodulating wild herbaceous legumes - Sadia Latif; SamiUllah Khan; Muhammad Naveed; Ghulam Mustafa; Tasmia Bashir; Abdul Samad Mumtaz (Archives of Microbiology, 2013)

Erratum to: Development of Controlled-Release Matrix Tablet of Risperidone: Influence of Methocel®- and Ethocel®-Based Novel Polymeric Blend on In Vitro Drug Release and Bioavailability - Amir Badshah; Fazal Subhan; Khalid Rauf; Nadeem Irfan Bukhari; Kifayattullah Shah; Samiullah Khan; Zia Ahmed; Ihsanullah Khan (AAPS PharmSciTech, 2011)

Development of Controlled-Release Matrix Tablet of Risperidone: Influence of Methocel®- and Ethocel®-Based Novel Polymeric Blend on In Vitro Drug Release and Bioavailability - Amir Badshah; Fazal Subhan; Khalid Rauf; Nadeem Irfan Bukhari; Kifayatullah Shah; Samiullah Khan; Zia Ahmed; Ihsanullah Khan (AAPS PharmSciTech, 2011)

The influence of gibberellic acid and sulfur fertilization rate on growth and S-use efficiency of mustard (Brassica juncea) - N. A. Khan; M. Mobin; Samiullah (Plant and Soil, 2005)

Utilization of Petrochemical Industry Waste Water for Agriculture - Ozair Aziz; Arif Inam; Samiullah (Water, Air, & Soil Pollution, 1999)